Pengaruh penerapan metode pembelajaran diskusi db tanya jawab terhadap minat belajar siswa pada kelas X MAN Dairi - Syah Rina Maha (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
In the teaching and learning process, teachers are required to be able to determine effective learning methods which aim to expedite the process and student learning outcomes so that what has been planned can be achieved well and easily by students. The discussion method is learning that confronts students with a problem. The main aim of this method is to solve problems, answer questions and find out students' knowledge and make decisions. Meanwhile, the question and answer method is a way of presenting learning in the form of questions that must be answered from the teacher to the students or from the students to the teacher. This type of research is descriptive research with a qualitative approach. The method used is data collection, namely observation sheets of teaching and learning activities based on designs, activities and observations, and journal literature. The results of this research are that students are able to participate in learning enthusiastically, this is shown by the number of students who try to share assignments with fellow groups, discuss parts they do not understand, ask questions, and look for answers. Keywords : Fun Method of Discussion and Question and Answer